Age and provenance of the Mio-Pleistocene sediments from the Sacaco area, Peruvian continental margin. (June 2022) - Ochoa, Diana; DeVries, Thomas J.; Quispe, Kelly; Barbosa-Espitia, Angel; Salas-Gismondi, Rodolfo; Foster, David A.; Gonzales, Renzo; Revillon, Sidoine; Berrospi, Raul; Pairazamán, Luis; Cardich, Jorge; Perez, Alexander; et al.
Abstract: Over the last decades, rocks from the East Pisco Basin (EPB), on the Central Peruvian coast (13°-16°S), have yielded an abundant and diverse collection of coastal-marine fossils, which are key for characterizing the onset and evolution of the modern Humboldt Current. Despite its paleontological richness, and after almost 40 years of study, the spatio-temporal context of the deposits of the southern part of the EPB (Sacaco area) remains only broadly constrained, being mostly tailored to particular vertebrate-rich levels occurring throughout the area. Here we build a composite stratigraphic section for the Sacaco area including three lithostratigraphic units (Pisco, Caracoles, and Pongo formations), which documents several discontinuities and intraformational unconformities. We infer depositional ages based on new radiometric (U–Pb), isotopic (Sr) and biostratigraphic data, synthesize previous litho-, chemo-, and bio-stratigraphic studies, and present a comprehensive chronostratigraphic review of the Mio-Pleistocene record for the Sacaco sub-basin that allows us to identify various local and basinal events. Our results indicate that, in the Sacaco area, the Pisco Formation ranges from ∼9.6 to 4.5 Ma, the overlying Caracoles Formation from 2.7 to ∼1.9 Ma, and the Pongo Formation accumulated from ∼1.9 up to at least 1.4 Ma. These sedimentary successions accumulated in a continually subsiding setting and show a shallowing-upwards trend. Zircon U–Pb provenance analysis mainly record Neoproterozoic, Cretaceous, and Mio-Pleistocene populations, revealing discrete up-section changes in source areas. Mio-Pleistocene and Cretaceous sources are continuously present, while older recycled-orogen sources vary through time in presence and abundance, indicating either paleogeographic changes or source exhaustion. Highlights: A chronostratigraphic framework for the Mio-Pleistocene record from Sacaco is presented. Insights on Mio-Pleistocene sediment sources are defined by provenance data. Discrete provenance changes occur up-section, especially at 6 Ma. Combined subsidence and tectonic uplift controlled the sediment accumulation in Sacaco.